1998
DOI: 10.1007/978-3-7091-6499-0_29
|View full text |Cite
|
Sign up to set email alerts
|

Effects of N-propargyl-1-(R)aminoindan (rasagiline) in models of motor and cognition disorders

Abstract: Summary. N-propargyl-1-(R)aminoindan (rasagiline) is a new and selective irreversible MAO-B inhibitor, currently being considered as the mesylate salt for potential therapy in certain neurological disorders. It has been studied in animal models of cognition and motor dysfunction. Its ability to restore normal motor activity was determined in models of acute drug-induced dopaminergic dysfunction: Its effects in improving cognition and memory deficits was studied in adult and senescent rats that had been exposed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
33
0

Year Published

2000
2000
2009
2009

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 72 publications
(35 citation statements)
references
References 17 publications
2
33
0
Order By: Relevance
“…21,28 In addition, both rasagiline and its metabolite 1(R)-aminoindan protected against ␣-methyl-p-tyrosine-induced hypokinesia in rats previously exposed to hypoxia. 30 We conducted this double-blind, randomized, placebo-controlled trial as a pilot study to evaluate the safety and tolerability of orally administered rasagiline, and to make a preliminary assessment of its efficacy, when administered as once-daily monotherapy (1, 2, or 4 mg/ day) in patients with early PD and who were not receiving L-dopa. This trial was supported by Teva Pharmaceuticals.…”
mentioning
confidence: 99%
“…21,28 In addition, both rasagiline and its metabolite 1(R)-aminoindan protected against ␣-methyl-p-tyrosine-induced hypokinesia in rats previously exposed to hypoxia. 30 We conducted this double-blind, randomized, placebo-controlled trial as a pilot study to evaluate the safety and tolerability of orally administered rasagiline, and to make a preliminary assessment of its efficacy, when administered as once-daily monotherapy (1, 2, or 4 mg/ day) in patients with early PD and who were not receiving L-dopa. This trial was supported by Teva Pharmaceuticals.…”
mentioning
confidence: 99%
“…29 Rodent models have also demonstrated improvements in motor function after drug-induced dopaminergic dysfunction, and in motor and cognitive function post-hypoxia. 30 Furthermore, rasagiline-treated mice had faster recovery of motor function and spatial memory, and less cerebral edema, after closed head injury. Stroke models in the rat demonstrated decreased infarct sized after MCA occlusion and improved neurological severity scores in multiple models.…”
Section: Evidence For Potential Neuroprotectionmentioning
confidence: 95%
“…(40) In contrast to selegiline, rasagiline is not metabolized to potentially toxic amphetaminic metabolites and its major metabolite, 1-R-aminoindan, has exhibited beneficial effects in animal models of PD. (50) Because of its selectivity towards MAO-B, rasagiline does not trigger the ''cheese effect'', (51) and was found to improve motor and cognitive function in PD animal models. (50) A recent clinical trial demonstrated the beneficial influence of rasagiline monotherapy in early stages of Parkinson's disease.…”
Section: Apoptosis and Parkinson's Diseasementioning
confidence: 99%
“…(50) Because of its selectivity towards MAO-B, rasagiline does not trigger the ''cheese effect'', (51) and was found to improve motor and cognitive function in PD animal models. (50) A recent clinical trial demonstrated the beneficial influence of rasagiline monotherapy in early stages of Parkinson's disease. (40) To evaluate the safety and efficacy of rasagiline, a multicenter clinical trial was carried out in which a total of 404 patients in early stages of PD were included.…”
Section: Apoptosis and Parkinson's Diseasementioning
confidence: 99%
See 1 more Smart Citation